PERTUNJUKAN MENUBUHKAN SENI(NYA INDONESIA) DAN RESPON PENONTON - Murcahyanto, hary; HD, Dharma Satrya (Universitas Hamzanwadi, 2016)
This study focused on the creative process and the audience response that refer to the post-colonial and post-modern theory. The method used is discourse analysis. The performance of Indonesia art processed during a month, which is in the lecturing process conducted during four meetings. The creative process starts from the discourse about the body and embody. The body discourse as a tool and goal. Body shown is the body of dance and drama, with another sentence is to embody the dance and Indonesian drama. The dances are performed is a dance of Papua, Kalimantan, Java, Bali, Indonesia, and Sasak. The sixth area was a representation of Indonesian art. The next show is a drama of White Blue Love then ended with a dance and Gugur Mayang music. The creative process based on the ability of setting up objects, events, pantomime and processes involving multimedia. All performances are getting response from the audience. There is good and less good respond. Some said exceptional, cool, fun, exciting, and entertaining. The responses indicate a logical reasoning about the stage and sense reasoning about the effect of the show. Another interpretation of these events in perspective post structuralism with refers to post structuralism Bartes and Foucoult and refers to post modernism Jameson and Lyotard, that the show was not be seen as a tradition or modernity, but an event with post-space, at the crossroads between tradition and modernity. The show speaks to the value.Keywords: Indonesia Art, Audience Response, Post-Structuralism, Post-Modernism